Diagnosing Arterial Stiffness in Pregnancy and Its Implications in the Cardio-Renal-Metabolic Chain - Vladiana-Romina Turi; Constantin Tudor Luca; Dan Gaita; Stela Iurciuc; Izabella Petre; Mircea Iurciuc; Tunde Horvath; Dragos Cozma (Diagnostics, 2022)
Cardio-renal and metabolic modifications during gestation are crucial determinants of foetal and maternal health in the short and long term. The cardio-renal metabolic syndrome is a vicious circle that starts in the presence of risk factors such as obesity, hypertension, diabetes, kidney disease and ageing, all predisposing to a status dominated by increased arterial stiffness and alteration of the vascular wall, which eventually damages the target organs, such as the heart and kidneys. The literature is scarce regarding cardio-renal metabolic syndrome in pregnancy cohorts. The present paper exposes the current state of the art and emphasises the most important findings of this entity, particularly in pregnant women. The early assessment of arterial function can lead to proper and individualised measures for women predisposed to hypertension, pre-eclampsia, eclampsia, and diabetes mellitus. This review focuses on available information regarding the assessment of arterial function during gestation, possible cut-off values, the possible predictive role for future events and modalities to reverse or control its dysfunction, a fact of crucial importance with excellent outcomes at meagre costs.